2021
DOI: 10.3390/children8020159
|View full text |Cite
|
Sign up to set email alerts
|

A First Step toward the Clinical Application of Landmark-Based Acoustic Analysis in Child Mandarin

Abstract: As an initial step for the clinical application of landmark-based acoustic analysis in child Mandarin, the study quantified the developmental trajectories of consonants produced by four-to-seven-year-old children who acquired Taiwanese Mandarin as their first language. The results from a total of 80 children (20 in each age group, with gender balanced) indicated that younger age groups produced more +b landmark features than seven-year-olds did, showing that the development of obstruents was not completed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Table 1. Acoustic rules and articulatory interpretations of the six abrupt-consonantal landmarks (adopted from MacAuslan [41], Ishikawa, MacAuslan and Boyce [42], and Liu [30]). [39] and Ishikawa and MacAuslan [43]).…”
Section: Mnemonicmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1. Acoustic rules and articulatory interpretations of the six abrupt-consonantal landmarks (adopted from MacAuslan [41], Ishikawa, MacAuslan and Boyce [42], and Liu [30]). [39] and Ishikawa and MacAuslan [43]).…”
Section: Mnemonicmentioning
confidence: 99%
“…Table 1. Acoustic rules and articulatory interpretations of the six abrupt-consonantal landmarks (adopted from MacAuslan [41], Ishikawa, MacAuslan and Boyce [42], and Liu [30]). Empirical studies using the software SpeechMark© have shown that the numbers of these acoustic landmarks could quantify the production traits of different populations and were highly correlated with the speech intelligibility of both typical and atypical populations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations